Experimental and numerical analysis of the performance and exhaust gas emissions of a biogas/n-heptane fueled HCCI engine. (15th November 2016) - Kozarac, Darko; Taritas, Ivan; Vuilleumier, David; Saxena, Samveg; Dibble, Robert W.
Abstract: The use of highly reactive fuel as an ignition promoter enables operation of biogas fueled homogeneous charge compression ignition (HCCI) engine at low intake temperatures with practical control of combustion phasing. In order to gain some insight into this operation mode the influence of addition of n-heptane on combustion, performance, emissions and control of combustion phasing of a biogas fueled HCCI engine is experimentally researched and presented in this paper. Additionally, the performance analysis of the practical engine solution for such operation is estimated by using the numerical simulation of entire engine. The results showed that the introduction of highly reactive fuel results with a significant change in operating conditions and with a change in optimum combustion phasing. The addition of n-heptane resulted in lower nitrogen oxides and increased carbon monoxide emissions, while the unburned hydrocarbons emissions were strongly influenced by combustion phasing and at optimal conditions are lowered compared to pure biogas operation. The results also showed a practical operation range for strategies that use equivalence ratio as a control of load. Simulation results showed that the difference in performance between pure biogas and n-heptane/biogas operation is even greater when the practical engine solution is taken into account. Highlights: The influence of n-heptane port fuel injection on biogas fueled HCCI was researched. The injection of n-heptane enables control of combustion timing. The injection n-heptane reduces peak rate of heat release and prolongs combustion. The injection of n-heptane increases the overall system efficiency.